2022
DOI: 10.1182/bloodadvances.2022007378
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity next-generation sequencing MRD assessment in ALL identifies patients at very low risk of relapse

Abstract: Measurable residual disease (MRD) is highly prognostic for relapse and overall survival (OS) in acute lymphoblastic leukemia (ALL), although many patients with apparent "MRD negativity" by standard assays still relapse. We evaluated the clinical impact of a highly sensitive next-generation sequencing (NGS) MRD assay in 74 adults with ALL undergoing frontline therapy. Among remission samples that were MRD negative by multiparameter flow cytometry (MFC), 46% were MRD positive by the NGS assay. After one cycle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 35 publications
2
22
1
Order By: Relevance
“…The combination of ponatinib and hyper‐CVAD resulted in the highest CMR rate reported so far (exclusive of the blinatumomab and TKI experiences) explaining why, for the first time in the history of Ph‐positive ALL therapy, allogeneic SCT may not be necessary in most patients, particularly in those who achieve a CMR 31 . Using more sensitive techniques to detect MRD, like next‐generation sequencing (NGS) that assesses clonal immunoglobulin heavy chain or T‐cell receptor rearrangements with a sensitivity of 10 −6 , may define better subsets of patients who may or may not benefit from allogeneic SCT in first CR 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of ponatinib and hyper‐CVAD resulted in the highest CMR rate reported so far (exclusive of the blinatumomab and TKI experiences) explaining why, for the first time in the history of Ph‐positive ALL therapy, allogeneic SCT may not be necessary in most patients, particularly in those who achieve a CMR 31 . Using more sensitive techniques to detect MRD, like next‐generation sequencing (NGS) that assesses clonal immunoglobulin heavy chain or T‐cell receptor rearrangements with a sensitivity of 10 −6 , may define better subsets of patients who may or may not benefit from allogeneic SCT in first CR 32 …”
Section: Discussionmentioning
confidence: 99%
“…31 Using more sensitive techniques to detect MRD, like next-generation sequencing (NGS) that assesses clonal immunoglobulin heavy chain or T-cell receptor rearrangements with a sensitivity of 10 À6 , may define better subsets of patients who may or may not benefit from allogeneic SCT in first CR. 32 Several investigators reported underlying genomic lesions in Ph-positive ALL that significantly influence outcomes, such as deletions of IKZF1 and CDKN2A/B. [33][34][35][36] However, these studies were performed in patients receiving earlier generation TKIs (e.g., imatinib or dasatinib).…”
Section: Discussionmentioning
confidence: 99%
“…within the first cycle of therapy) and more sensitive next-generation sequencing-based MRD assays (sensitivity of) may help to select those who could potentially safely discontinue TKI. 43 , 44 Identification of patients who may safely discontinue TKI therapy is important because of the potential for long-term toxicity with all BCR::ABL1 TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low levels of MRD by NGS, but negative MRD by MFC, still had a significant risk of relapse (5-year CIR: 39%). 20 Another study examined the association between MRD levels and influence hematopoietic cell transplantation (HCT) outcomes in children. Using an International Pediatric ALL MRD database, the authors examined peri-HCT MRD by either MFC or allele-specific oligonucleotide (ASO)-PCR in over 600 children.…”
Section: Depth Of Mrd Assessment and Association With Outcomesmentioning
confidence: 99%